Sources of labour productivity growth in manufacturing industries in Malaysia / Ernie Abu (Faculty of Business and Management, 2008)
Manufacturing sector plays an important role in the Malaysian economic development. Manufacturing sector also provide a broad marketing channel to Small and Medium Industries (SMls) which subsequently spur linkages within the industria! sector. Apart from this, manufacturing sector also serve as a platform for foreign direct investment (FDI) that could potentially lead to technology transfer. Since manufacturing plays an important role in development, it is crucial to identify and understand the sources of labour productivity growth in this sector. This paper attempts to analyze the sources of labour productivity growth in manufacturing industries in Malaysia. Three sources of growth identified in this paper are capital-labour ratio, quantity of labour and efficiency which usually traced to two broad factors. First, contribution from physical inputs namely capital-labour ratio and the quantity of labour and second, contribution from improved efficiency due to technological advancement and other factors that may increase the quality of inputs. The analyses in this paper are based on the Manufacturing Industrial Survey data of 1975 to 2004 collected by the Department of Statistics Malaysia.